Follow-up evaluation of first two cohorts of graduates of the Zambian HIV nurse practitioner program. (2015) - Mulenga, Universe H.; Chanda, Dorothy; Gashongore, Ignace; Katayamoyo, Patrick; Masebe, Esther Mukokomena; Mukanyimi, Bosco; Mukupo, Florence; Mulenga, Lloyd; Mulenga, Priscilla L.; Musamba, Beatrice; Mutemi, Dorothy; Mwanahamuntu, Flora Hainde; et al.
Abstract: Background: This paper presents findings from a follow-up evaluation of the 63 graduates of the first two cohorts of an HIV Nurse Practitioner (HNP) program that was initiated in Zambia in 2009. Methods: This was a descriptive study that incorporated a mixture of quantitative and qualitative data collection methods. A structured interview guide was used to collect data during structured interviews with 40 of the 63 graduates of the HNP program, 39 of their supervisors, and 49 of their patients. In addition 566 charts were audited to assess the quality of care provided by the graduates. Results: Findings indicate that the graduates were assuming the expanded roles for which they were prepared, and many were working in other units in addition to the ART clinic. Patients reported a high level of satisfaction with the quality of care provided by the graduates, and reported that the graduates were providing quality care. The data from the chart audits indicated that although the graduates are generally documenting and providing care appropriately, there are areas that should be improved and emphasized in refresher courses and in the future HNP educational programs. Conclusions: Findings are consistent with findings from the limited number of other published studies suggesting that nurses can provide high-quality care for patients with HIV and AIDS. Further research is recommended to assess the impact of such programs on morbidity and mortality indicators, and on staff retention and job satisfaction of nurses and also of the HNPs.